Ngān songs̄œm Sinlapawatthanatham Thabūang Mahāwitthayālai, khrang thī 2, 1-3 Thanwākhom, Ph̨̄o. S̨̄o. 2542, Mahāwitthayālai Rāmkhamh̄æng (Mahāwitthayālai Rāmkhamh̄æng, 1999)
Volume brought out at 2nd fair to promote Thai art and culture of the Ministry of University Affairs, organized by Ramkhamhaeng University; comprises works chiefly on Thai culture.